Capital Stock Depreciation, Tax Rules, and Composition of Aggregate Investment - Daniel Levy (Journal of Economic and Social Measurement, 1995)
I estimate time varying aggregate capital stock depreciation rates for the post-war U.S. economy using capital-investment evolution equation along with the data on the annual net capital stock and corresponding quarterly gross investment series. I estimate depreciation rates of consumer durable goods, producer durable goods, and nonresidential business structures. The estimation results suggest that the three depreciation rate series have been behaving very differently over time. In particular, I find that over time the implied depreciation rate of nonresidential business structures has remained stable, the implied depreciation rate of consumer durable goods has been steadily declining, while the implied depreciation rate of producer durable goods has been increasing, especially during the last 10–15 years. These findings are interpreted in terms of the changes in the composition of the aggregate nonresidential business fixed and producer durable good capital stocks. In addition, I discuss the implications of the changes introduced during the 1980s in rules and regulations governing a depreciation accounting for tax purposes, and their effect on the estimates of capital depreciation rates derived in this paper. The main argument the paper makes is that technological progress may be leading to accelerated depreciation of producer durable goods and equipment since newer and more advanced technology makes older equipment obsolete. The empirical evidence reported in this paper supports this argument.
Keywords: E22; C82; 330; Time Varying Depreciation Rate; Capital Stock; Consumer Durable Goods; Producer Durable Goods; Business Structures; Technological Progress